2019
DOI: 10.3390/ma12213628
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of ANFIS-PSO and ANFIS-GA Models in Predicting Thermophysical Properties of Al2O3-MWCNT/Oil Hybrid Nanofluid

Abstract: The main purpose of the present paper is to improve the performance of the adaptive neuro-fuzzy inference system (ANFIS) in predicting the thermophysical properties of Al2O3-MWCNT/thermal oil hybrid nanofluid through mixing using metaheuristic optimization techniques. A literature survey showed that the use of an artificial neural network (ANN) is the most widely used method, although there are other methods that showed better performance. Moreover, it was found in the literature that artificial intelligence m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…On the other hand, Wang et al [10] employed a fuzzy multicriteria decision-making model (MCDM) for raw material supplier selection in the plastic industry. Likewise, Lin et al [11] applied fuzzy collaborative intelligence approach for fall detection in four existing smart technology applications and a methodology for obtaining technological mean roughness (Ra) for the EDM process, Alarifi et al [42] employed genetic algorithms and particle swarm optimization to determine the parameters of an ANFIS model to predict the thermo-physical properties of Al 2 O 3 -MWCNT/thermal oil hybrid nanofluid and an analysis of the PSO implementation in designing parameters of manufacturing processes as well as a benchmark with other optimization techniques can be found in the review study of Sibalija [43]. On the other hand, Alajmi et al [44] used an ANFIS-QPSO to predict the surface roughness of the dry and cryogenic turning process of AISI 304 stainless steel.…”
Section: State Of the Artmentioning
confidence: 99%
“…On the other hand, Wang et al [10] employed a fuzzy multicriteria decision-making model (MCDM) for raw material supplier selection in the plastic industry. Likewise, Lin et al [11] applied fuzzy collaborative intelligence approach for fall detection in four existing smart technology applications and a methodology for obtaining technological mean roughness (Ra) for the EDM process, Alarifi et al [42] employed genetic algorithms and particle swarm optimization to determine the parameters of an ANFIS model to predict the thermo-physical properties of Al 2 O 3 -MWCNT/thermal oil hybrid nanofluid and an analysis of the PSO implementation in designing parameters of manufacturing processes as well as a benchmark with other optimization techniques can be found in the review study of Sibalija [43]. On the other hand, Alajmi et al [44] used an ANFIS-QPSO to predict the surface roughness of the dry and cryogenic turning process of AISI 304 stainless steel.…”
Section: State Of the Artmentioning
confidence: 99%
“…Using only a single hidden layer, the MLP-ANN showed an R 2 value equal to 0.99974. Alarifi et al [47] measured the thermal conductivity behaviour of Al 2 O 3 -MWCNT/thermal oil hybrid nanofluids; in predicting the behaviour of the nanofluids, the ANFIS was optimised with genetic algorithms (GA) and particle swarm optimisation. The study concluded that while both models could predict thermal conductivity in the hybrid to a significant degree of accuracy; the ANFIS optimised with PSO had a better predictive performance compared to the ANFIS model optimised by GA.…”
Section: Introductionmentioning
confidence: 99%
“…It continuously extends its base of knowledge through the addition of new rules which makes the system upgrading easier and faster with no need for long shutdowns [19]. To achieve optimum MG energy operation and control, metaheuristic optimization algorithms such as the genetic algorithm (GA) and particle swarm optimization (PSO) are further proposed for training the ANFIS [20].…”
Section: Introductionmentioning
confidence: 99%